Patogénesis de la babesiosis bovina ocasionada por la babesia bigemina y alteraciones macro y microscópicas (1978)
Fifteen calves were inoculated with Babesia bigemine to study macroscopic and microscopic lesions In this one month experiment the calves were euthanatized and dissected every other day. The macroscopic findings inciuded yellowish icterus discoioration of the aponeurotic and subcutaneous tissue, petechial hemorrhages on serous surfaces, excess of penicardial, pleural and peritoneal fluid, which color turned from ambar to yellow reddish. These alterations were observed in the calves dissected at days, 6, 10, 12 and 14 P1. An increase in size of the parotid, mandibular, suprapharingeal, preescapular, mediastinic, splenic, mesentenic, prefemoral and renal lymph nodes was seen in the calves at days 4, 10, 12, 16, 18, 20, 22 and 24 P1. The spleen was three times its normal size in the calf dissected at day 12 P1. Microscopically vascular congestion and leukocyte margination were observed in all the tissues studied. Macrophages with hemosiderin, erythrophagocitosis, hyalin degeneration in arteries, lymphoid and reticular atrophy and hyperplasia were observed in the lymph nodes since day 6 P1, to day 30 PT. Similar lesions were present in the spleen, hemal lymph nodes and tonsiis. Portal lymphoid infiltration, severe leukocyte margination in hepatic veins and portal arteries were observed at days 24, 26, 28 and 30 P1. Kupffer cell hyperplasia was observed since day 6 PT and persisted during the experiment. Leukocyte margination in the central nervous system was evident since day 12 P1 until day 30 P1. Vascular congestion, edema and perivascular and peribronchiolar hemorrhages in the pulmonary tissue were observed from day 6 Pb to day 26 P1. Leukocyte margination, endothelial hyperplasia and perivascuiar and periglomerular lymphoid infiltration were observed in the kidneys since day 8 P1 until day 30 P1. Macroscopic and microscopic alterations in calves which suffered Babesiosis were described.